2023
DOI: 10.1093/mnras/stad535
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the mass spectrum of destroyed dwarf galaxies with the metallicity distribution function

Abstract: Accreted stellar populations are comprised of the remnants of destroyed galaxies, and often dominate the ‘stellar haloes’ of galaxies such as the Milky Way (MW). This ensemble of external contributors is a key indicator of the past assembly history of a galaxy. We introduce a novel statistical method that uses the unbinned metallicity distribution function (MDF) of a stellar population to estimate the mass spectrum of its progenitors. Our model makes use of the well-known mass-metallicity relation of galaxies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Another possible scenario is that these star-forming regions could have been actual UFD galaxies. This idea is supported by the recent work of Deason et al (2023), who found that the stellar metallicity distribution of Sextans could allow for the accretion of multiple UFD-like systems. Much larger samples of stars at large radius will be necessary to distinguish among these scenarios.…”
Section: Chemical Inhomogeneity In Sextansmentioning
confidence: 73%
See 1 more Smart Citation
“…Another possible scenario is that these star-forming regions could have been actual UFD galaxies. This idea is supported by the recent work of Deason et al (2023), who found that the stellar metallicity distribution of Sextans could allow for the accretion of multiple UFD-like systems. Much larger samples of stars at large radius will be necessary to distinguish among these scenarios.…”
Section: Chemical Inhomogeneity In Sextansmentioning
confidence: 73%
“…Studies by Chiti et al (2021Chiti et al ( , 2023, Filion & Wyse (2021), Longeard et al (2022Longeard et al ( , 2023, Qi et al (2022), Yang et al (2022), and Sestito et al (2023aand Sestito et al ( , 2023b have shown that several dSph and UFD galaxies contain stars near their tidal radii. These extended stellar halos may have formed through dwarf galaxy mergers (Rey et al 2019;Tarumi et al 2021), and multiple mergers may have occurred within individual dSph galaxies around the Milky Way (Griffen et al 2018;Deason et al 2023). These stars frequently exhibit low metallicities, [Fe/H] < −2.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their proximity, the stellar halos of the Milky Way and M31 have thus far been our primary sources of data. Both halos are predominantly old and metal-poor (e.g., Unavane et al 1996;Chiba & Beers 2000;Kalirai et al 2006;Carollo et al 2007) but have been found to contain a substantial amount of substructure (Ibata et al 1994(Ibata et al , 2001a(Ibata et al , 2007Majewski et al 1996;Chiba & Beers 2000;Ivezić et al 2000;Yanny et al 2000;Newberg et al 2002;Ferguson et al 2002;Jurić et al 2008;Bell et al 2008;Gilbert et al 2012;Naidu et al 2020), some of which is chemically distinct from the bulk of the halo (e.g., Cohen et al 2018;Deason et al 2023). Although stars that likely originated in the central disks have been found in the stellar halos of both the Milky Way and M31 (e.g., Carollo et al 2007;Bonaca et al 2017), the general consensus is that most of their stars formed in satellites that were eventually tidally disrupted (e.g., Searle & Zinn 1978;Majewski et al 1996;Bullock et al 2001;Purcell et al 2007;Bell et al 2008), and differences between the halos can therefore generally be attributed to differences in their accretion histories.…”
Section: Introductionmentioning
confidence: 99%